Health Sciences Libraries: A Changing Landscape - Bolduc, Janet; Dyer, Elizabeth; Kerecman, Linda; McKelvy, Dina (Maine Policy Review, 2024)
Health sciences libraries provide specialized resources and services to learners, clinicians, patients and the community. The authors describe how health sciences libraries continue to evolve in a changing healthcare system landscape. New technologies, roles, educational resources and learner expectations provide challenges and opportunities for health sciences libraries.